Contracts for the National Health Service. - Chalkley, M; Malcomson, J (Department of Economics (University of Southampton), 1996)
This paper reviews the implications of the economic theory of contracts for contracting in National Health Service (NHS), focusing on contracts to maintain quality standards while keeping costs down.